Feed production, swine and slaughterhouse: where is the highest occupational exposure to Aspergillus spp. in this production line - Viegas, Carla (2016)
This study intended to characterize fungal contamination in two swine farms, in one feed production unit, and also in one swine slaughterhouse. We aimed to identify where the highest occupational exposure to Aspergillus spp. was detected during the production line. Air and surfaces samples were collected from the four units through impaction and swabbing methods, respectively. Quantitative and qualitative results were obtained, with the identification of the isolated fungal species. For molecular analysis, 300L of air were also collected from each same sampling site using the impinger method. Real Time quantitative PCR (qPCR) was done to perform the molecular detection of the Aspergillus sections Circumdati, Fumigati and Flavi (only the toxigenic strains). Results: Eleven species of filamentous fungi were identified in air samples from the feed production unit, with a total of 1666 isolates. None Aspergillus species were isolated. Seven filamentous fungi species were found in the slaughterhouse, with a total of 810 isolates and only 10 isolates belonging to the Aspergillus fumigatus group (section Fumigati) were isolated. Twelve fungal species were found in the air from one of the analyzed swine farms in a total of 3080 isolates. Aspergillus genus showed low prevalence (6.5%), being the sections Candidi, Circumdati and Terrei the only ones isolated. Regarding the other assessed swine farm, 15 fungal species were identified, in a total of 5080 isolates. Aspergillus genus presented the highest prevalence (15.7%). Among this genus, Eurotium herbariorum (section Restricti) was the most prevalent (45.0%). Fumigati and Circumdati sections were also isolated. Regarding the results obtained by molecular methods, A. fumigatus section was detected in 10 sampling sites where this species-complex was not isolated by conventional methods: 2 in feed production, 4 in slaughterhouse and 2 in each swine farm assessed. Cultural methods showed that swine farms were the settings with the highest fungal load, presenting also the highest number of isolates belonging to Aspergillus spp., and a more diversified number of sections. The applied molecular tools enabled to target selected fungal indicators of higher occupational risk, allowing a more accurate characterization on occupational exposure to Aspergillus.